PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KOPI KENANGAN DI DEPOK - Ahmad Rizky Firaza (2022)
This Research is a quantitative study which aims to determine the effect of brand image, product quality, and word of mouth on purchasing decision. The population in this study are consumers who have purchased and consumed Kopi Kenangan products in Depok. The numbers of samples taken was 75 respondents, with a probability sampling method using purposive sampling method, this research using questionaires to collect its data and used the PLS (Partial Least Square), for the analysis technique using SmartPLS 3.0 software. The results of this study indicate that (1) Brand image has a significant effect on purchasing decision, (2) Product Quality has a significant effect on purchasing decision, (3) Word of mouth has a significant effect on purchasing decisions.